Между диалогичностью и интертекстуальностью. Проблема текста в тексте на примере рассказа Бориса Лавренева Сорок первый - Chudzińska-Parkosadze, Anna (Acta Polono-Ruthenica, 2013)
The article deals with two kind of problems - the specification and differences between intertextuality defined by Kristeva and concept of dialogue defined by Bakhtin, on the one hand, and the presence of these key categories of the contemporary literary criticism in the story written by Boris Lavrenyov The Forty-First, on the other hand. The research refers also to the links between the theory of Kristeva and the poetic of ornamental prose, and shows the key role of parody in both of them. As the result the author comes to the conclusion that the story is being constructively divided into two parts, one of which has got an intertextual character and the other one dialogical. Moreover, the first category is related to parody, and Bakhtin’s concept of dialogue to tragic nature.